Uporabnost Vprašalnika za oceno izboljšanja zdravja (BHI2) za ocenjevanje napredovanja v poklicni rehabilitaciji - Jakopec, Zlatka (Rehabilitacija (Ljubljana), 2015)
Background: Along with activities aimed at the development of working abilities, vocational rehabilitation focuses on psychosocial rehabilitation, whose goals include the improving the quality of life, well-being, self-image and more effective coping with problems and limitations. The aim of our study was to determine whether persons undertaking vocational rehabilitation show signs of progress in various psychological and psychosocial factors, and if there are differences between people with positive and negative outcomes as well as between groups of people with mainly physical or mainly mental health problems. Methods: The study was conducted on a sample of 34 people who are undertaking vocational rehabilitation programs at the Centre for Vocational Rehabilitation Maribor. The participants were asked to complete the Battery for Health Improvement (BHI2) at the start and at the end of their rehabilitation. BHI2 has previously not been used in Slovenia. It is a standardised psychodiagnostic instrument, which was developed with the purpose of psychological evaluation of patients with physical health problems and the monitoring of changes during rehabilitation. Results: Rehabilitation with positive outcome (employment) was completed by 77% of the participants, while 23% of them were evaluated as unemployable at the end of rehabilitation. When compared to the results achieved at the start of the study, participants showed signs of progress in the areas measured by the BHI2 questionnaire at the end of rehabilitation. The most statistically significant progress (p<0.01) was achieved on the scales of Depression, Anxiety, Chronic Maladjustment, Survivor of Violence, Job Dissatisfaction and the reported level of maximum pain. We observed moderate progress (p<0.05) on the scales of Pain Complaints, Hostility, Borderline, Substance Abuse, Family Dysfunction and the reported level of minimum pain. Other scales showed trends of improvement, but the results were not statistically significant. Improved performance on the BHI2 questionnaire was linked to positive results in rehabilitation: the participants who were employed at the end of rehabilitation showed marked progress on the BHI2 scales, whereas those who were evaluated as unemployable did not. Conclusion: Our results indicate that rehabilitation has a positive influence in terms of the proportion of persons who manage to find employment as well as in terms of changes regarding the psychological and psychosocial factors and job satisfaction. We believe that the BHI2 is a useful tool for assessment of participants' needs and in the planning of rehabilitation, as it covers a wide spectrum of medical, psychological and psychosocial factors. It thus provides a comprehensive insight into an individual's condition, and repeated measurements allow us to monitor progress during rehabilitation.
Keywords: bolečina; Pain; physical factors; poklicna rehabilitacija; psihologija; psihološki dejavniki; psihosocialna podpora; psychological factors; Psychology; psychosocial support; Rehabilitation, Vocational; Social support; socialna podpora; telesni dejavniki